A Methodology for Determining Air Force Education Requirements Board (AFERB) Advanced Academic Degree (AAD) Requirements - Terry, Tara L. (RAND Corporation, 2013)
Predicting the number of Air Force billet vacancies that will require an advanced academic degree (AAD) can be difficult and can lead to inaccuracies that result in either a shortfall or an oversupply of officers with specific degrees and academic specialties. This report examines the process by which the Air Force matches personnel with AADs to billets requiring them, and it describes a methodology for improving this process.